2021
DOI: 10.1097/jom.0000000000002202
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Covid-19 in Global Health and Psychosocial Risks at Work

Abstract: Objective: The main objective is to understand and characterize the impact of Covid-19 pandemic on mental health and psychosocial risks at work in professionally active adults. Methods: This specific work includes 4708 professionally active participants from all over the country, of which 3354 are women (71.2%), aged between 19 and 86 years, with an average age of 45.8 years (SD = 12.56). Results: The global impact of Covid-19 is explained by soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 21 publications
(76 reference statements)
6
44
1
Order By: Relevance
“…Thus, VSW over 36 years old scored more in job insecurity, burnout, and offensive behaviour. These results are contrary to what was observed in the aforementioned Portuguese study developed by Gaspar et al [ 6 ], in which younger professionals, i.e., 35 years or less, present more PSR of work, greater impact of COVID-19 on work intensity, and negative evolution of health symptoms. Considering the characteristics of the sample in the present study, which is mostly comprised of women, it can be hypothesized that this could be a group of women with school-age children requiring greater support during the COVID-19 pandemic period and, consequently, experiencing greater difficulty in balancing job functions and family life [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Thus, VSW over 36 years old scored more in job insecurity, burnout, and offensive behaviour. These results are contrary to what was observed in the aforementioned Portuguese study developed by Gaspar et al [ 6 ], in which younger professionals, i.e., 35 years or less, present more PSR of work, greater impact of COVID-19 on work intensity, and negative evolution of health symptoms. Considering the characteristics of the sample in the present study, which is mostly comprised of women, it can be hypothesized that this could be a group of women with school-age children requiring greater support during the COVID-19 pandemic period and, consequently, experiencing greater difficulty in balancing job functions and family life [ 30 ].…”
Section: Discussioncontrasting
confidence: 99%
“…After the first lockdown, 44.9% of VSW advanced to mixed work, maintaining exposure to the aforementioned risks. Indeed, a Portuguese study developed by Gaspar et al [ 6 ] to analyse the impact of COVID-19 on global health and PSR at work concluded by the greatest PSR at work, namely the bulk of the responsibility, intellectual effort, multitasking, and overall stress. The association of these risks to work tasks, emotional and cognitive demands, health, and well-being enhances the vulnerability of workers and their greater difficulty in managing the personal and professional challenges caused by the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations